KARAKTERISTIK BISKUIT DENGAN PEMANFAATAN UMBI DAN PASTA DAUN SINGKONG (Manihot esculenta Cranz) - Paramitha, Ni Kadek Diah Ayu; Ina, Putu Timur; Pratiwi, I Desak Putu Kartika (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
The purposes of this research were to know the effect comparation of cassava flour and cassava leaves paste on the characteristics of biscuit and to know the right comparation from cassava flour and cassava leaves paste to produce biscuit the best characteristics. The experimental design was used randomized block design with the treatment comparation of cassava flour and cassava leaves paste that 95% : 5%, 92% : 8%, 89% : 11%, 86% : 14%, 83% : 17%; and 80% : 20%. The treatment was repeated as many as 3 times so that 18 experimental units were obtained. The data was analyzed with ANOVA and if the influential on variable observed continued with the Duncan test. The results showed that the comparation of cassava flour and cassava leaves paste significantly affected to water content, ash content, crude fiber content, chlorofil total, beta karoten total, and hedonic test (colour, aroma, texture, taste, and overall acceptance) and scoring test (texture). Comparation from cassava flour and cassava leaves paste (92% : 8%) is the best characteristics with water content is 2,77%, ash content was 2,58%, crude fiber content is 15,39%, chlorofil total is 22,93%, beta karoten total is 434,96% , color liked, flavor of cassava leaves liked, texture very crispy and liked, taste liked, and overall acceptance liked.